The exercise of parental responsibility and the protection of the child’s right to privacy on the internet and social networks - Mladenović, Tamara (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Abstract: The protection of the child’s right to privacy in the modern digital environment assumes an entirely new dimension. The development of technologies that occurred at the beginning of the twenty-first century has expanded the boundaries of the physical world into a boundless cyberspace. The rapid growth in the use of the Internet and social networks has profoundly transformed the very concept of privacy. Photos, videos, and other personal information are publicly shared via social networks with a significantly wider circle of people than was once the case. This practice particularly affects children, who in the online environment, from the status of subjects, granted by the adoption of the UN Convention on the Rights of the Child in the late 1980s, are once again reduced to objects of parental actions in online sphere. The phenomenon of so-called sharenting – excessive publication of children’s photos on social networks by parents – is becoming increasingly prevalent. In such instances, parents often disregard their duty to act as legal representatives of the child in his/hers best interests, perceiving themselves instead as the “owners” of their child’s data. Therefore, the child’s right to privacy extends beyond the protection of physical and psychological integrity in the modern era to include control over their digital identity and information that is permanently stored in virtual space. Although direct access to the Internet is often legally prohibited for the youngest and most vulnerable groups of people, they are increasingly present in digital environments indirectly - through their parents. Decisions regarding the publication of child’s personal data generally rest exclusively with the parents, while the child’s opinion is often disregarded, either due to parental negligence or because of the child’s age. Sharing children’s personal data on social networks raises questions about the limits of parental responsibility and the obligation to act in the best interests of the child. Legal complications are particularly evident in situations where parents disagree on whether a child’s images should be shared online. In this regard, the Supreme Court of Cassation of Serbia, in its judgment Rev 14012/2022, held that the publication of a child’s photographs by one parent, against the will of the other, is contrary to the principle of the best interests of the child. Given that this issue is not explicitly regulated by the legislation of the Republic of Serbia, lower courts have taken different positions on the above-mentioned case. Nevertheless, the Supreme Court of Cassation emphasized that, where the parent exercising sole parental responsibility opposes such publication, the act of the non-custodial parent constitutes a question of representation of the child by his or her legal guardian. At the same time, in this way, in the conflict between the rights of the child and the interests of the parents, the child’s right to privacy was given priority. Taking into account the age and maturity of the child, in certain cases the child’s opinion will play a significant role in decisions concerning his/her privacy. The right of the child to be heard, as one of the guiding principles of the Convention on the Rights of the Child, serves as an essential mechanism in balancing parental responsibility with the protection of the child’s privacy. Upon reaching the so-called “digital majority”, the child is considered sufficiently mature to exercise meaningful influence over the development of his or her own digital identity.